Cross-sectional study on aluminium in groundwater and health risk assessment in Orang Asli village in Batu 28, Jenderam Hilir, Selangor - Lina Abdul Jalil.
Introduction: The water supply from groundwater is not free from the impurities as there is no series of treatment process occurred since there was no maintenance available for this time being. Since the water supply is directly consumed from the source, there is potential effect of aluminium to be contained in the drinking water as a result of natural process. Chronic toxicity of aluminium in drinking water is related with the diseases associated with nerves system (dementia) such as Alzheimer's disease. The limit concentration of aluminium in drinking water set by Ministry of Health Malaysia in National Standard of Drinking Water Quality is 0.2 mg/L. Objective: To determine level of aluminium in drinking water in groundwater related to health risk assessment among population at Perkampungan Orang Asli Batu 28, Jenderam Hilir Selangor. Methodology: A cross-sectional survey had been conducted at Perkampungan Orang Asli Batu 28, Jenderam Hilir Selangor at one village with 100 respondents. The study population involved male and female respondents aged 18 and above, who used groundwater as their daily drinking water without any filtration in their houses. 200ml of drinking water from respondents' house was taken as sample, together with their body weight measurement. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze aluminium concentration and LAMOTTE TRACER ORP PockeTester for measuring pH level. Statistical Package for Social Science (SPSS) was used to analyze the data. Results and Discussions: The range of aluminium concentration was 0.046 - 0.19 mg/L, hence aluminium level in drinking water was below the standard value. The HI<1, thus there was no health risk of A1 exposure in drinking water and there was a significant relationship between aluminium and pH value in drinking water. Conclusion: The study found that the level of aluminium concentration did not exceed the standard. Even though the pH level was found acidic, since HI<1, therefore, the study area was considered safe from having risk associated with nervous system.